2021
DOI: 10.3390/su13063206
|View full text |Cite
|
Sign up to set email alerts
|

Firefly Algorithm-Based Photovoltaic Array Reconfiguration for Maximum Power Extraction during Mismatch Conditions

Abstract: This studyaimed at improving the performance and efficiency of conventional static photovoltaic (PV) systems by introducing a metaheuristic algorithm-based approach that involves reconfiguring electrical wiring using switches under different shading profiles. Themetaheuristicalgorithmused wasthe firefly algorithm (FA), which controls the switching patterns under non-homogenous shading profiles and tracks the highest global peak of power produced by the numerous switching patterns. This study aimed to solve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…This article [18] provides a method for MPPT of a photovoltaic panel array with partial shadowing using an improved pattern search method. The firefly algorithm (FA) [19] is a control mechanism for switching patterns in non-homogeneous shading profiles that follows the largest global peak of power generated by many switching patterns. The article then introduces a novel, intelligent, bio-inspired meerkat optimization algorithm [20] (MOA) capable of finding the global power peak and assuring maximum power supply.…”
Section: Introductionmentioning
confidence: 99%
“…This article [18] provides a method for MPPT of a photovoltaic panel array with partial shadowing using an improved pattern search method. The firefly algorithm (FA) [19] is a control mechanism for switching patterns in non-homogeneous shading profiles that follows the largest global peak of power generated by many switching patterns. The article then introduces a novel, intelligent, bio-inspired meerkat optimization algorithm [20] (MOA) capable of finding the global power peak and assuring maximum power supply.…”
Section: Introductionmentioning
confidence: 99%
“…PV module interconnections are modified based on the firefly algorithm (FA) method to disperse the shading effect on the PV array. Higher GMPPs are achieved at 1155.18, 1175.91, 1654.18, 1670.65, 1314.68, and 1552.95 W compared to series parallel and TCT configurations under various shading scenarios such as downward corner (DL), X‐shape, double side (DS), C‐shape, quadra corner (QC), and Tetris shape (TS) 27 . In Rezk et al, 28 coyote optimization algorithm (COA) is shown to have the best performance compared to flower pollination algorithm (FPA)‐, MPA‐, and BOA‐based PV array configurations.…”
Section: Introductionmentioning
confidence: 99%
“…27 FA• Simple, flexible, and easy to implement.• Lack of creativity with an extensive analogy Rezk et al 28 COA • Able to solve multiobjective problems • High convergence speed • Inferior search capabilities…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive Bank TCT : i × j Scanning algorithm V, I 2(i * j) [30] Adaptive Reconfiguration SP: 3 × 3 Firefly algorithm V, I 2(i * j) ) technique to overcome the PSC of a 9 × 9 TCT PV system using EAR. The method was compared with conventional TCT and SDK puzzle PR methods for the power improvement of the PV array [23].…”
Section: Introductionmentioning
confidence: 99%